Humanitarian invasion : global development in Cold War Afghanistan - Nunan, Timothy, 1985- 1985- (Global and international history, 2016)
Humanitarian Invasion is the first book of its kind: a ground-level inside account of what development and humanitarianism meant for Afghanistan, a country touched by international aid like no other. Relying on Soviet, Western, and NGO archives, interviews with Soviet advisers and NGO workers, and Afghan sources, Timothy Nunan forges a vivid account of the impact of development on a country on the front lines of the Cold War. Nunan argues that Afghanistan functioned as a laboratory for the future of the Third World nation-state. If, in the 1960s, Soviets, Americans, and Germans sought to make a territorial national economy for Afghanistan, later, under military occupation, Soviet nation-builders, French and Swedish humanitarians, and Pakistani-supported guerrillas fought a transnational civil war over Afghan statehood. Covering the entire period from the Cold War to Taliban rule, Humanitarian Invasion signals the beginning of a new stage in the writing of international history